Transgenerational effects and temperature variation alter life history traits of the moon jellyfish - Chi, Xupeng; Zhang, Fang; Sun, Song (Frontiers in Marine Science, 2022)
Understanding life history strategy of organisms is key to predicting their populations dynamics. The population of scyphozoan jellyfish displays an increasing trend in recent decades, yet its life history strategy has been not fully understood. To interpret reproduction strategy of scyphozoan jellyfish from an evolutionary ecology perspective, we dissected 10 asexual generations of Aurelia coerulea polyps to investigate relationships between transgenerational effects on their budding reproduction and strobilation. Our results revealed that polyp’s average budding reproduction rate declined 32.82% through asexual generations within the experimental time. Furthermore, longer culture duration counteracted the transgenerational effects on budding rates and strobilation afterward. Thus, this effort provides insight into the necessity of sexual reproduction in organisms involving a metagenic life cycle, i.e., to renew their asexual reproduction ability of a population. Besides, we suggest to take the caution that it is necessary to know the “asexual age” of polyps when performing experimental studies and mathematical modeling to explore their population dynamics. Our results also present a valuable dataset to interpret the evolution of scyphozoan jellyfish’s life history strategy under multifactorial environments.